The Influence of Head Teacher's Leadership Style on Junior High School Students ' Learning Engagement: The Mediating Effect of Self-efficacy - Quan, Guixian (Transactions on Social Science, Education and Humanities Research, 2024)
As a class leader, junior high’s head teachers play an imperative and essential role in the development of junior high students and the whole class. Based on this reason, the aim of this research is to investigate the effect of the head teachers’ leadership style on junior high students’ learning engagement, inspecting mediating effect of self-efficacy. The study used three authority scales, they are teacher leadership style scale, academic self-efficacy scale and study engagement scale. With these scales, the study finally launches the research on the influence of head teacher's leadership style on middle school students’ learning engagement and the role of self-efficacy in mediating. The results from this study are as follows. First, authoritative teacher leadership style and democratic teacher leadership style are positively correlated with junior high students’ self-efficacy and learning engagement. Second, learning engagement is significantly affected by self-efficacy. Third, self-efficacy plays the intermediary role between democratic and authoritative teacher leadership styles and junior high students’ learning engagement. As a conclusion, this research suggests head teachers should improve junior high students’ self-efficacy by making changes to their leadership style so that they can have a positive influence on their students’ learning input. Additionally, head teachers are suggested to carry out a democratic and authoritative teacher’ s leadership style, instead of a laissez-faire teacher’ s leadership style. For example, the head teacher is bound to protect students’ self-esteem and respect the individual differences.